Experimental investigation of mechanical properties on CF reinforced PLA, ABS and Nylon composite part. (2023) - Venkatesh, R.; Jerold John Britto, J.; Amudhan, K.; Anbumalar, V.; Prabhakaran, R.; Thiyanesh Sakthi, R.
Abstract: The goal of this research was to compare the physical and mechanical properties of Polylactic acid (PLA), Acrylonitrile Butadiene Styrene (ABS), and Nylon manufactured using fused deposition modelling (FDM) and conventional injection modelling techniques. The mechanical characteristics of fused deposition modelling are influenced by a number of factors. If the components are for commercial use, this might be a critical consideration. The impact of nozzle temperature and infill line orientations on items manufactured using short carbon fibre (CF)-reinforced polylactic acid is the topic of this research.PLA, ABS, Nylon, PLA-CF, ABS-CF, and Nylon-CF composite test bars were created under precisely controlled settings. The strengthening action of high modulus CFs results in Nylon-CF having stronger tensile characteristics than Nylon. For both Nylon and Nylon-CF, a nozzle temperature of 245 °C achieved maximum tensile characteristics. As a result, this temperature was chosen to investigate the impact of infill orientations in test bars. In comparison to the other orientations, the combination [0°/15°/-15°] relative to the long axis of the test bar offers the greatest value of tensile characteristics for both Nylon and Nylon-CF.